2011
DOI: 10.35690/978-2-7592-1656-7
|View full text |Cite
|
Sign up to set email alerts
|

Insectes ravageurs des graines de légumineuses

Abstract: Adulte femelle de Callosobruchus maculatus F. du morphe non-voilier (l : 3 à 5 mm). © Irbi Tours. 6. Callosobruchus maculatus F., femelle (avec taches noires sur les élytres), mâle (sans taches sur les élytres), du morphe voilier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 147 publications
(217 reference statements)
1
14
0
1
Order By: Relevance
“…The results showed that the sexual maturity of females increased along with the density of flowers, leading to ovipositioning on first pods sets. The results corroborated the laboratory observations of Huignard et al ( 4 ). Thus, for weevils, flowers were a meeting place for mating, which could explain the lack of sexual pheromones (Frérot, personal communication).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that the sexual maturity of females increased along with the density of flowers, leading to ovipositioning on first pods sets. The results corroborated the laboratory observations of Huignard et al ( 4 ). Thus, for weevils, flowers were a meeting place for mating, which could explain the lack of sexual pheromones (Frérot, personal communication).…”
Section: Discussionsupporting
confidence: 92%
“…Typically, adults first feed on the plant pollen, then females lay eggs on pods, and finally, larvae feed and develop into the seeds. Therefore, in Fabaceae, the plant phenology, such as blooming and pod setting, are components of the selective pressure driving the optimal physiological development of bruchid beetles ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 25.60% of larvae from C. serratus eggs died at the larval stage, as they were unable to weave cocoons. Larvae that have reached the 4 th stage emerged from the seeds to weave C. serratus cocoons for pupation ( [26], although some larvae may weave cocoons inside the seed. This low rate of emergence is due to larval mortality caused by inter-larval competition, caused by the supernumerary population of larvae in the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Ces espèces de bruches nuisibles aux stocks de légumineuses sèches peuvent accomplir plusieurs générations par an, indifféremment dans les réserves de graines sèches ou dans les cultures de légumineuses-hôtes E x e m p l a i r e a u t e u r en y allant pondre au moment de la formation des gousses. Ces espèces sont de véritables fléaux pour les réserves de légumineuses et elles peuvent y occasionner des dégâts importants pouvant dépasser 30 % de perte pondérale sur niébé (Huignard et al, 2011).…”
Section: Les Bruches Des Légumineuses (Famille Des Bruchidés)unclassified